Nafs Wahidah Dalam Al-Qur’an Al-Karim Menurut Zaghlul Raghib Muhammad An-Najjar - Akbar, Ahmad Fadly Rahman; Rifaannudin, Mahmud; Badrun, Muhammad; Nuraini, Nuraini Maghfiroh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
The difference in the meaning of Nafs Wahidah in the Qur'an is a problem still a hot topic of discussion among mufassir. Through this research, the writer sees Zaghlul An-Najjar as one of the scientific commentators who interpret the meaning of Nafs Wahidah from a scientific point of view. Therefore, the author research and discuss how Zaghlul An-Najjar interprets Nafs Wahidah in the Qur'an. This research is library research, while the method used is scientific thematic interpretation (dirasah maudhu'iyah 'ilmiyah). Results of research Nafs Wahidah according to Zaghlul An-Najjar in Q.S An-Nisa: 1 and Q.S Az-Zumar: 6 is a unit of inheritance that comes from Adam's rib in the form of Deoxyribose Nucleic Acid (DNA) and Mitochondria. Human DNA stores human genetic information and is then carried by RNA, which is in charge of conveying genetic information to the next generation. In addition, lafazh